Doping in Sport and the Law - Haas, Ulrich; Healey, Deborah (Hart Publishing Ltd, 2016)
This unique international legal and cross-disciplinary edited volume contains analysis of the legal impact of doping regulation by eminent and well known experts in the legal fields of sports doping regulation and diverse legal fields which are intrinsically important areas for consideration in the sports doping landscape. These are thoughtful extended reflections by experts on theory and policy and how they interact with law in the context of doping in sport. It is the first book to examine the topical and contentious area of sports doping from a variety of different but very relevant legal perspectives which impact the stakeholders in sport at both professional and grass roots levels. The World Anti-Doping Code contains an unusual mix of public and private regulation which is of more general interest and fully explored in this work. Each of the 14 chapters addresses doping regulation from a legal perspective such as tort, corporate governance, employment law, human rights law, or a scientific area. Legal areas are generally considered from an international and not national perspective. Issues including fairness, logic and the likelihood of compliance are explored. It is vital reading for anyone interested in the law, regulation and governance of sport.